Abnormal fatty acid metabolism is a core component of spinal muscular atrophy. Issue 8 (26th July 2019) - Deguise, Marc‐Olivier; Baranello, Giovanni; Mastella, Chiara; Beauvais, Ariane; Michaud, Jean; Leone, Alessandro; De Amicis, Ramona; Battezzati, Alberto; Dunham, Christopher; Selby, Kathryn; Warman Chardon, Jodi; McMillan, Hugh J.; et al.
Abstract: Objective: Spinal muscular atrophy (SMA) is an inherited neuromuscular disorder leading to paralysis and subsequent death in young children. Initially considered a motor neuron disease, extra‐neuronal involvement is increasingly recognized. The primary goal of this study was to investigate alterations in lipid metabolism in SMA patients and mouse models of the disease. Methods: We analyzed clinical data collected from a large cohort of pediatric SMA type I–III patients as well as SMA type I liver necropsy data. In parallel, we performed histology, lipid analysis, and transcript profiling in mouse models of SMA. Results: We identify an increased susceptibility to developing dyslipidemia in a cohort of 72 SMA patients and liver steatosis in pathological samples. Similarly, fatty acid metabolic abnormalities were present in all SMA mouse models studied. Specifically, Smn 2B/‐ mice displayed elevated hepatic triglycerides and dyslipidemia, resembling non‐alcoholic fatty liver disease (NAFLD). Interestingly, this phenotype appeared prior to denervation. Interpretation: This work highlights metabolic abnormalities as an important feature of SMA, suggesting implementation of nutritional and screening guidelines in patients, as such defects are likely to increase metabolic distress and cardiovascular risk. This study emphasizes the need for a systemic therapeutic approach to ensure maximal benefits for all SMA patients throughout their life.